Mitochondrial DNA lineages and genetic variation of early growth traits in the Argentinean breeding population of Pinus ponderosa Douglas ex C. Lawson - Aparicio, Alejandro Gabriel; El Mujtar, Veronica Andrea; Azpilicueta, Maria Marta; Martinez Meier, Alejandro; Mondino, Victor Alejandro (Springer, 2024)
In the Andean-Patagonian region of Argentina, Pinus ponderosa Douglas ex C. Lawson is the most widely cultivated forest tree species. Its breeding program, started in 1998, is now progressing towards the establishment of 1.5 generation clonal seed orchards. Considering recent advances in the phylogeny and taxonomy of the species, it is necessary to delve deeper into the genetic variation of the breeding population. Here, we first aim to address a previously unresolved question concerning the putative genetic lineages (varieties) of P. ponderosa that were introduced from the USA. We assessed this question through the molecular characterization of the nad1 second intron minisatellite of the mitochondrial genome of 61 plus trees planted in 1.0 clonal seed orchards, followed by Sanger sequencing to determine mtDNA haplotypes. Then, we conducted a nursery common garden trial to determine the relative contribution of the genetic factors (lineages and clones) to the variation in early growth traits, which may reflect adaptation across native geographic ranges and are also important for nursery stock production. We found three mtDNA variants, which correspond to haplotypes H1, H5 and H8, form the North-West native range of the species. In general, the variation in early seedling growth traits was not attributable to the haplotypic groups; instead, variation among clones was high and heritable. Considering the initial performance of the breeding population, it appears feasible to manage 1.0 and 1.5 clonal seed orchards by maintaining sub-specific taxa mixed together, while assessing the potential impact of intra-specific hybridization and field performance of progeny for timber production and resilience to climate change.